The role of differences in trematode invasion of male and female viviparids (Mollusca, Gastropoda, Viviparidae) of Central Polesia in reproduction of their populations - E.I. Uvayeva; G.Kh. Shcherbina; E.D. Shimkovich (Учёные записки Казанского университета: Серия Естественные науки)
Trematode invasion of Viviparus viviparus (Lіnné, 1758) and V. contectus (Millet, 1813) populations from the region of Central Polesia (Ukraine) was analyzed. It was revealed that the total rates of trematode (parthenitae and larvae) infection in the viviparid populations under study differ between males and females. Age-related differences were also found: the trematode prevalence was higher in younger female and older male viviparids. It was suggested that differences in the infection rates of male and female molluscs by trematodes is a way to effectively control the parasite–host interaction at the population level in order to hold up the stability of host reproduction. The obtained results demonstrate that the viviparid populations maintain a high reproduction level, because trematodes infect such age and gender groups that are least important in the reproduction process.